Role of TERT Gene in Relationship between Body Fat Percentage with the Modifiable Risk Factors of Cardiometabolic Disease in Minangkabau Premenopausal - Lestari, Yuniar; Sulastri, Delmi; Desmawati, Desmawati (Open Access Macedonian Journal of Medical Sciences, 2020)
Background: Cardiometabolic disease risk is increasing in the premenopausal phase of women life. This study aims to relationship body fat percentage with the modifiable risk factors of cardiometabolic disease in Minangkabau premenopausal people. Methods: A cross-sectional study was conducted in 111 Minangkabau premenopausal people, aged 40 â€“ 55 years old at Padang City in West Sumatera, Indonesia. Body fat percentage analyzed by Bioelectrical Impedance Analyzer (BIA). Fasting blood glucose and lipid profile was examined from venous blood. Data were analyzed by using a Rank-Spearman correlation test with significant levels p<0.05. Results:Average body fat percentage of subjects 36.23 Â± 6.9, fasting blood glucose 101.52 Â± 12.3 mg/dL; total cholesterol 193.99Â±41.5 mg/dL; triglyceride 113.76Â±37.9 mg/dL mg/dL; LDL-cholesterol 120.59Â±45.7 mg/dL and HDL-cholesterol 53.52Â±15.6 mg/dL. Body fat percentage has a significant correlation with triglyceride (r=0.368; p=0.001), and HDL-cholesterol levels (r=-0.307; p=0.006 ) just in subject with polymorphism, but does not have a significant correlation with another biomarker. Conclusion: Body fat percentage correlates with triglyceride and HDL cholesterol in Minangkabau premenopausal women who have polymorphism of TERT Gene. BACKGROUND: Cardiometabolic disease risk is increasing in the premenopausal phase of women life. The telomerase reverse transcriptase (TERT) gene is a gene that plays a role in protecting telomeres from progressive shortening. Telomere shortening is associated with the incidence of cardiometabolic disease. AIM: This study aims to elucidate the relationship body fat percentage with the modifiable risk factors of cardiometabolic disease in Minangkabau premenopausal people. METHODS: A cross-sectional study was conducted in 111 Minangkabau premenopausal people aged 40–55 years old at Padang City in West Sumatera, Indonesia. Body fat percentage analyzed by bioelectrical impedance analyzer. Fasting blood glucose and lipid profile were examined from venous blood. Polymorphism of the TERT rs2736098 gene was analyzed by a polymerase chain reaction. Data were analyzed using Spearman’s rank correlation test with significant levels p < 0.05. RESULTS: Average body fat percentage of subjects was 36.23 ± 6.9, fasting blood glucose was 101.52 ± 12.3 mg/dL; total cholesterol was 193.99 ± 41.5 mg/dL; triglyceride was 113.76 ± 37.9 mg/dL; LDL-cholesterol was 120.59 ± 45.7 mg/dL and HDL-cholesterol was 53.52±15.6 mg/dL. Body fat percentage has a significant correlation with triglyceride (r = 0.368; p = 0.001) and HDL-cholesterol levels (r = −0.307; p = 0.006) just in subject with polymorphism but does not have a significant correlation with another biomarker. CONCLUSION: Body fat percentage correlates with triglyceride and HDL cholesterol in Minangkabau premenopausal women who have polymorphism of TERT gene.